Oceanic Fronts Shape Biodiversity of Gelatinous Zooplankton in the European Arctic - Mańko, Maciej K.; Merchel, Malgorzata; Kwasniewski, Slawomir; Weydmann-Zwolicka, Agata (Frontiers in Marine Science, 2022)
Oceanic fronts constitute boundaries between hydrologically distinct water masses and comprise one of the most productive regions of the world’s ocean. Fronts associated with density gradients (active fronts) profoundly structure planktonic communities in adjacent waters, but less is known about the impacts of density-compensated (passive) fronts. Two such fronts are found in the European Arctic, the Arctic Front (AF) and the Polar Front (PF), that both separate warmer and saltier, Atlantic water from the colder, but fresher Arctic water. As scrutinized research on the influence of passive fronts on zooplankton at large spatial and temporal scales had been lacking, we tackled the question of their role in maintaining distinct communities, employing globally unique, 12-year-long gelatinous zooplankton (GZ) and hydrological time series from the European Arctic. The GZ, owing to their fast reproductive cycles and passive dispersal, reflect particularly well the local environment. We therefore compared GZ communities between zones separated by the two fronts, disentangled their drivers, and analyzed community shifts occurring whenever front relocation occurred. We have identified fifteen GZ taxa, distributed among three distinct communities, specific for front-maintained zones, and selected the following taxa as indicators of each zone: W—west of the AF, within the Greenland Sea Gyre, Beroe spp.; C—central, in between the AF and the PF, Aglantha digitale; and E—east of the PF, in the West Spitsbergen Shelf Mertensia ovum. Taxonomic composition of these communities, and their specific abundance, persisted throughout time. We also showed that relocation of either front between the sampling years was subsequently followed by the restructuring of the GZ community. Our results indicate that passive oceanic fronts maintain distinct GZ communities, with probable limited exchange across a front, and provide a new perspective for the Arctic ecosystem evolution under progressing Atlantification.